Hemorragia postparto en primipara de 27 años - Garrido Dulcey, Jamileth Silvana (2019)
Postpartum hemorrhage is considered as one of the main obstetric complications, which can cause maternal death especially in underdeveloped countries, it should be noted that this complication can be prevented in many cases if it is diagnosed in time and if the active management steps are followed correctly of the third stage of labor. There are several complications that can cause postpartum hemorrhage, including uterine atony, and traumas at the level of the birth canal that are the most prevalent pathologies, but there are other causes such as coagulopathies. Most cases in which this complication occurs within 24 hours after delivery. Although it is very important to identify in the postpartum patients, whether physiological or surgical, their antecedents and risk factors that can cause postpartum hemorrhage, although it is important to highlight that in many cases postpartum hemorrhage occurs without the patient having had risk factors that predispose her to suffer it.